Evaluation of Physiotherapy students' knowledge about professional identity in two Spanish public universities. - Ramírez-Pérez, Laura; García-Conejo, Celia; Escriche-Escuder, Adrián; Corrionero-Ramírez, Victoria; Moreno-Morales, Noelia; Roldán-Jiménez, Cristina (My University, 2024)
Introduction: Physiotherapy is an autonomous and regulated profession. However, pseudo-health professions treat patients despite lacking formal training and certificates. This fact provokes confusion between patients, professionals, and students, which can represent a decrease in the quality of care practice and a risk to patient safety. The objective was to analyze the prior knowledge and beliefs of first-year students of the Degree in Physiotherapy to identify the identity aspects of the profession associated with knowledge gaps. Methodology: This study recruited students from 2 Spanish public universities. In the first session, the students anonymously completed a digital questionnaire, which included questions related to professional identity, its scope of application, its therapeutic instruments, and its legal and scientific basis. Additionally, potential confounding factors were identified, such as the existence of medical relatives, to improve the interpretation of the results. Results: 245 students participated. Physiotherapy is identified as a health profession (99.6%), although the criteria that define health professions are not known by 32.7% of the students. Physiotherapists are distinguished by students compared to other professionals such as massage therapists or osteopaths. However, there are doubts about whether or not other pseudo-healthcare professions are categorized as health disciplines. It is largely considered that Physiotherapy, as a profession, should be guided by scientific evidence. Likewise, there are doubts regarding the competencies and some physiotherapy techniques. Conclusions: Although physiotherapy students access university training with certain knowledge, there are still some deficiencies especially related to the competencies, the differences between Physiotherapy and pseudo-health professions, and the requirements to consider a profession as health. Informative content that addresses these deficiencies should be promoted.
Keywords: Investigación activa en educación; Fisioterapia - Estudio y enseñanza superior; Education; Knowledge; Physiotherapy